1999
DOI: 10.1099/0022-1317-80-9-2527
|View full text |Cite
|
Sign up to set email alerts
|

PrP gene polymorphism and natural scrapie in Icelandic sheep

Abstract: The association between scrapie and polymorphism of the prion protein (PrP) gene was studied in the Icelandic sheep breed. Polymorphism of the three codons, 136, 154 and 171, that are important for scrapie susceptibility was determined. A BspHI restriction analysis was used to study the alleles of codons 136 and 154, while density gradient gel electrophoresis (DGGE) was used to analyse codon 171 and detect new polymorphisms. The PrP allelic variant, VRQ (amino acids at codons 136, 154 and 171), was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
3
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 27 publications
6
91
3
4
Order By: Relevance
“…When comparing averages from different breeds in different countries the AHQ allele frequency range appears to be 0.2% (USA) [21] to 12.5% (Norway) [68,88]. The mean of the AHQ frequency for the 20 studies (see above) is 6.3% and regional frequencies are 2.5% for Italy and Spain [1,2,4,27], 3.8% for Iceland [86], 9.6% for Greece [12,24] and 7.1% for New Zealand [14]. These data suggest that susceptible genotypes are available in most populations and also that genetic screening could be used for susceptibility control.…”
Section: Atypical Scrapie In Sheepmentioning
confidence: 96%
See 2 more Smart Citations
“…When comparing averages from different breeds in different countries the AHQ allele frequency range appears to be 0.2% (USA) [21] to 12.5% (Norway) [68,88]. The mean of the AHQ frequency for the 20 studies (see above) is 6.3% and regional frequencies are 2.5% for Italy and Spain [1,2,4,27], 3.8% for Iceland [86], 9.6% for Greece [12,24] and 7.1% for New Zealand [14]. These data suggest that susceptible genotypes are available in most populations and also that genetic screening could be used for susceptibility control.…”
Section: Atypical Scrapie In Sheepmentioning
confidence: 96%
“…A survey conducted for this review of more than 20 studies [1,2,4,14,20,21,23,24,27,38,54,64,68,69,82,83,[86][87][88]90] reporting on sheep populations from 15 different countries in Europe, America and Asia revealed that so far all but one (Iceland) presented significant frequencies of all five major alleles (ARQ; ARR; AHQ; VRQ; ARH) in their sheep. Iceland appears not to have any ARR animals [86]. The allele frequency averaged over all animals in these studies were 56% ARQ, 30% ARR, 6% AHQ, 5% VRQ and 3% ARH.…”
Section: Classical Scrapie In Sheepmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHQ, ARH, ARQ, and VRQ alleles are generally associated with susceptibility. The degree of, and the ranking for, susceptibility appears to be breed dependent, with the VRQ allele (when present within a breed) generally considered the most susceptible [7,8,31,44,61,64,77,79]. There is also evidence to suggest that polymorphisms at other codons within the PrP gene may modify the degree of resistance associated with the ARQ allele [82].…”
Section: Introductionmentioning
confidence: 99%
“…There is much evidence for the role of the PrP genotype in susceptibility to scrapie and in determination of the incubation period. 15,23,53,54 There is less direct evidence for the role of genotype in the type of clinical pattern shown, although the form of clinical expression may be determined by genotype and influenced by strain type. The effects of agent strain and host genotype on PrP Sc accumulation in the brain have been reported.…”
Section: File # 10emmentioning
confidence: 99%